2018
DOI: 10.1002/jwmg.21485
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the migration behaviors of pronghorn on their northern range

Abstract: Migration functions as an adaptive strategy to improve fitness by allowing individuals to exploit spatiotemporal gradients of resources. Yet migration, especially among large ungulates, is increasingly threatened by human activities, making it necessary to understand variation in migratory behavior. We identified different movement strategies for pronghorn (Antilocapra americana) at the northern limit of the species’ range, and tested hypotheses for variation between migratory behaviors. From 2003–2010, we cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 51 publications
2
73
0
Order By: Relevance
“…The study area experienced severe winter conditions from 2008 to 2011, especially during the winter of 2010–2011, when mean temperatures were below average and snow accumulation broke regional records (Jakes et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area experienced severe winter conditions from 2008 to 2011, especially during the winter of 2010–2011, when mean temperatures were below average and snow accumulation broke regional records (Jakes et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…, Jakes et al. ). Studies of partially migratory populations can provide key insights into behavioral and fitness consequences between movement tactics (Cagnacci et al.…”
Section: Introductionmentioning
confidence: 99%
“…Usually viewed as a predictable displacement between a specific breeding area and a specific non‐breeding area (Newton ), migratory movements can nevertheless show interannual variations and may vary between individuals in terms of direction and distance travelled (Berthold et al , Bauer et al ). In ungulates, although migration can be a fixed behaviour (Sawyer et al ), migratory plasticity has received increasing support in recent years (Mysterud et al , Eggeman et al , Jacks et al , Spitz et al ) and flexibility in migratory behaviour has been observed in individuals switching between different migratory strategies (Morrison and Bolger , Eggeman et al , Spitz et al ). Such variability makes the conservation of highly mobile species particularly challenging (Runge et al ).…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, flexibility in migratory behaviour allows individuals to adjust their migratory strategies switching between migrant and resident status according to the expected gain in fitness of each tactic (Eggeman et al ). Flexibility in migratory behaviour reflects the effects of environmental conditions observed at the population level because individuals switch from residents to migrants based on competition and resources availability (Eggeman et al , Jacks et al ). Such flexibility in migratory behaviour allows individuals to be more resilient to environmental changes (Gilroy et al ) and less exposed to perturbations than individuals in populations with fixed migratory behaviour (Harris et al , Sawyer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Pronghorn on the other hand, utilize a much larger swath of winter range habitats (~125 km 2 ; Figure 1) and move about often and unpredictably (Bruns, 1977;Collins, 2016;Kolar, Millspaugh, & Stillings, 2011;Sawyer, Lindzey, & McWhirter, 2005). The challenges associated with detecting behavioral changes in highly mobile species can be accentuated by short-term study, especially in regions prone to variable weather events and environmental conditions (e.g., Jakes et al, 2018). The challenges associated with detecting behavioral changes in highly mobile species can be accentuated by short-term study, especially in regions prone to variable weather events and environmental conditions (e.g., Jakes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%